Obama's Leading from behind Approach in MENA and Political Stability in Libya - Farkash, Majda (Dirasat: Human and Social Sciences, 2022)
The main concern of the paper is to explore how Obama's leading approach from behind or low engagement approach in MENA has contributed to the instability and crippling of the political transition in Libya. The paper employs the descriptive method to pursue and analyze the implications of Obama's leading-from-behind approach to political stability and transition in Libya. The paper uses the defensive realism theory in an attempt to explain Obama's leading-from-behind approach in MENA. The paper found that Obama's leading from-behind approach had three direct implications on the instability and crippling of the political transition in Libya: first, military intervention to topple Ghaddafi Regime without a plan for political transition, which was required in a very complex case like the Libyan case. Second, the absence of the U S's active role and leaving Libya with very weak and divided European leadership. Third- U.S.'s inaction to prevent the regional powers from spoiling UNSMIL's efforts. Accordingly, the Obama administration bears the largest share of the instability and crippling of the political transition in Libya.